Identification of the structural characteristics, optical properties, and adsorption performance of Bi and Sn co-doped Co0.5Zn0.5Fe2O4 nanoparticles - Sajida Rmeid; Amani Aridi; Khulud Habanjar; Sherif G. Elsharkawy; Ramadan Awad (South African Journal of Chemical Engineering, 2025)
Highly effective techniques, such as adsorption, play an important role in removing hazardous pollutants from wastewater. Spinel ferrite nanoparticles have proven to be effective adsorbents for removing dyes from wastewater. Thus, the preparation, characterization, and application of (Co0.5−xZn0.5−xBixSnx)Fe2O4 nanoparticles (0 ≤ x≤ 0.1) as adsorbents for brilliant blue dye removal were reported in this study. The XRD analysis confirmed sample purity with minimal hematite phase. The synthesized nanoparticles exhibit spherical morphology, as revealed by SEM analysis. Additionally, EDX measurements revealed the successive substitution of the Co2+ and Zn2+ host ions by Bi2+ and Sn2+ dopants. UV–vis spectroscopy analysis yielded an increase in the direct and indirect bandgap energies upon co-doping. Among the prepared nanoparticles, the highest recombination rate was exhibited by (Co0.5−xZn0.5−xBixSnx)Fe2O4 nanoparticles with x= 0.02, while the slowest recombination rate was observed for x= 0.04, as revealed from photoluminescence (PL) analysis. Adsorption experiments examined the effects of contact time, adsorbent dosage, pH, temperature, and initial dye concentration. Co-doped ferrite nanoparticles demonstrated efficient dye removal under various conditions. Kinetic and isotherm studies revealed a favourable adsorption process, following pseudo-second-order kinetics and best fitting the Freundlich isotherm. These findings highlight the potential of co-doped ferrite nanoparticles as effective adsorbents for wastewater treatment.